Soil Fungal Diversity Loss and Appearance of Specific Fungal Pathogenic Communities Associated With the Consecutive Replant Problem (CRP) in Lily - Shi, Guiying; Sun, Hongqiang; Calderón-Urrea, Alejandro; Jia, Xixia; Yang, Hongyu; Su, Guoli (Frontiers in Microbiology, 2020)
Edible lily (Lilium davidii var. unicolor) has economic value in China, particularly in Gansu Province, due to its uses as food and in gardening. Edible lily is usually cultivated in a long-term continuous monoculture resulting in the so-called consecutive replant problem (CRP), which is associated with severe soil degradation and significant yield and quality losses. This study was conducted to investigate the fungal community structure and specific fungal members related to lily’s CRPs using metabarcoding analysis. Fungal diversity of rhizosphere soil was analyzed by high-throughput DNA sequencing (Miseq) of samples collected in fields at 0, 3, 6, and 9 replant years (L0, L3, L6, and L9, respectively). The results show that long-term replanting significantly decreased both soil fungal diversity and abundance at the OTUs levels. Furthermore, replanting altered the soil microbial communities, where 4 to 5 years of replanting is a key transition period for substantial change of fungal community structure, resulting in new fungal community structures in L6 and L9 compared to in L0 and L3. The fungal diversity loss and fungal community structure simplification contributes to the negative effect of replanting in lily, and after 6 years of replanting, accumulation of highly abundant pathogenic fungal genera and depletion of the putative plant-beneficial fungal genera exacerbate the lily CRP. In addition, changes in the soil physiochemical properties strongly contributes to the new structure of fungal communities, and the genera Cryptococcus and Guehomyces could be regarded as potential indicators to monitor and manage sustainable soil health in the lily cropping system.